O jardim itinerante como instrumento facilitador no processo de ensino-aprendizagem de botânica no ensino médio - Santos, Leonardo Lima dos (2019)
The content of Botany for basic education in Brazil is still taught through a traditional method, which prioritizes conventional ways of communication. It is basically theoretical and transmissive, giving excessive value to the content and its conceptual aspects. This merely descriptive way of teaching in the basic school environment can generate a low stimulus and disinterest on the part of the students and teachers. The current work presents a project of construction of an itinerant garden, which helps facilitating the teaching of Botany in formal and non-formal environments. The garden is designed as a tray with dimensions appropriate to be carried in the trunk of a popular car. Plant species with a didactic profile were chosen to help to create a meaningfull learning relationship through a playfull and investigative proposal. The plants were grouped in the main taxonomic groups: non-vascular plants, ferns, naked seed plants and flowering plants. The experimental application took place in the National Science and Technology Week (SNCT) and in a state educational unit, located in the city of Rio de Janeiro, Brazil. The qualitative evaluation showed the students' high degree of learning commitment in the contact with the itinerant garden, helping to build the teaching of Botany. We expect that the use of the garden would contribute to a better integration of the knowledge by the students, collaborating to the formation of critical and skilled students.